Rib Hyperostosis as a Risk Factor for Poor Prognosis in Cervical Spine Injury Patients With Diffuse Idiopathic Skeletal Hyperostosis. Issue 5 (1st March 2020) - Sawakami, Kimihiko; Watanabe, Kei; Sato, Tsuyoshi; Miura, Kazuto; Katsumi, Keiichi; Hosaka, Noboru; Nomura, Shinsen; Fujikawa, Ryuta; Kikuchi, Ren; Tashi, Hideki; Minato, Keitaro; Segawa, Hiroyuki; et al.
Abstract : Study Design: Retrospective multi-center study. Objective: To identify the morphological features of costovertebral joints and ribs in surgically managed cervical injury patients with diffuse idiopathic skeletal hyperostosis (DISH) and to examine its impact on their vital prognosis. Summary of Background Data: Several reports have indicated that DISH is an independent risk factor for mortality after spinal fracture. The reason for the high mortality in cervical injury patients with DISH is unclear, although some reports have suggested a possible association between pulmonary complications and mortality. Methods: From 1999 to 2017, a total of 50 DISH patients (44 males) with cervical spine injuries who underwent spinal surgery were enrolled (average age 74 yrs). Prognosis and clinical risk factor data were collected; the morphological features of the patients' costovertebral joints and ribs were evaluated with computed tomography. The influence of each proposed risk factor and thoracic morphological feature on mortality was tested with univariate and multivariate analyses. Results: The survival rate at 5 years after surgery was 52.3%. Nineteen (38%) patients died, and the most common cause of death was pneumonia (68%). Costovertebral bone excrescences and rib hyperostosis were found to be thoracic pathognomonic signs; their frequencies were 94% and 82%, respectively, and these conditions occurred in an average of 7.0 joints and 4.7 bones, respectively. The results of the log-rank test showed a significant difference in age, injury severity score (ISS), costovertebral bone excrescences, and rib hyperostosis. The results of age-adjusted multivariate analysis indicated that age (hazard ratio [HR] = 8.65, 95% confidence interval [CI] = 1.10–68.28, P = 0.041) and rib hyperostosis (HR = 3.82, 95% CI = 1.38–10.57, P = 0.010) were associated with mortality. Conclusion: Reduced chest wall mobility associated with rib hyperostosis in cervical spine injury patients with DISH leads to a poor prognosis. Level of Evidence: 3 Abstract : Fifty diffuse idiopathic skeletal hyperostosis (DISH) patients with cervical spine injuries were investigated to identify the morphological features of costovertebral joints and ribs. The secondary objective was to examine the impact of DISH on vital prognosis. Reduced chest wall mobility and rib hyperostosis in cervical spine injury patients with DISH lead to poor prognosis.